Trends and characteristics in barbiturate deaths Australia 2000–2019: a national retrospective study. (4th March 2021) - Campbell, G.; Darke, S.; Zahra, E.; Duflou, J.; Shand, F.; Lappin, J.
Abstract: Introduction: There have been increasing reports documenting barbiturate-related deaths, despite routine prescribing for only relatively rare indications. The aims of the current study were to examine trends in barbiturate-related deaths in Australia from 2000 to 2019 and determine the case characteristics and circumstances of barbiturate-related deaths. Methods: All barbiturate-related deaths identified in the Australian National Coronial Information System were examined. Information was collected on cause, manner, demographics, location, psychosocial factors, circumstances of deaths and toxicology. We examined these based on the age categories 18–44 years, 45–64 years and ≥65 years. Results: We identified 511 cases. Mean age was 57.9 years (SD 20.2, range 18–100) and 56% were male. Intentional poisoning was the most common cause of death (87.5%) and was slightly higher in the oldest age group (92.1%) and lowest in the youngest age group (81.1%). Pentobarbitone was the most common barbiturate (75.7%) and pentobarbitone-related deaths increased from 0% in 2000 to 93.6% in 2017. There were notable differences between age categories, with the youngest age group recording more severe psychiatric histories. In contrast, the oldest age group were more likely to have severe physical health problems, such as cancer, chronic non-cancer pain, neurological conditions and significant cardiopulmonary morbidity. Euthanasia resources were commonly documented (33.9%), most frequently in the oldest age group (52.3%). Conclusion: Barbiturate-related deaths in Australia are increasing, particularly pentobarbitone-related deaths. Most deaths were intentional and involved adults across the lifespan. Younger people were more likely to have significant mental health problems, whilst the oldest age group were more likely to have severe physical health conditions.